PENGARUH TERPAAN MEDIA SOSIAL TIKTOK @NDSHVV TERHADAP BRAND AWARENESS PRODUK CAMILLE BEAUTY(Survei Penelitian pada Generasi Z Di Jakarta) - Qusnul Khotimah Meiana Putri, (2022)
This study is a quantitative study that aims to determine how much influence TikTok @Ndshvv social media exposure has on brand awareness of Camille Beauty products. Camille Beauty itself is one of the organic skincare products from Indonesia which experienced an increase in sales during the Covid-19 pandemic, namely the period from 2019 to 2022. By maximizing various forms of promotion through TikTok social media on the @Ndshvv account, it can make the wider community especially Gen Z, which is the generation that uses TikTok the most, is more aware of the existence of Camille Beauty products, and can increase buying interest in these products. The theory used in this research is advertising exposure theory. The theory generally discusses the exposure of a media will bring up certain attitudes and feelings towards the brand (brand). The population in this study is Generation Z in Jakarta who are users of TikTok social media. The sample size was taken as many as 100 respondents using a non-probability sampling technique, the type of purposive sampling. Data was collected through the distribution of online questionnaires using google form. The data analysis technique used is inferential statistical analysis, using a tool for testing, namely SPSS Version 25. Based on the coefficient of determination test, the results show that TikTok @Ndshvv social media exposure has a 41.7% effect on brand awareness of Camille Beauty products in generation z in Jakarta. These results can be strengthened by the results of the hypothesis test or t test which shows that H1 is accepted and H0 is rejected, which can be interpreted if there is a significant influence on TikTok @Ndshvv social media exposure to brand awareness of Camille Beauty products in generation z in Jakarta. Keywords: Media Exposure, TikTok, Brand Awareness.